2021
DOI: 10.7150/ijbs.59117
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms in chemotherapy for pancreatic cancer: An overview of current research and future directions

Abstract: Pancreatic cancer is a malignant tumor of the digestive system with a very high mortality rate. While gemcitabine-based chemotherapy is the predominant treatment for terminal pancreatic cancer, its therapeutic effect is not satisfactory. Recently, many studies have found that microorganisms not only play a consequential role in the occurrence and progression of pancreatic cancer but also modulate the effect of chemotherapy to some extent. Moreover, microorganisms may become an important biomarker for predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 172 publications
(209 reference statements)
0
10
0
Order By: Relevance
“…Elevated levels of oral pathogens Agregatibacter actinomycetemcomitans and Porphyromonas gingivalis , which may affect resistance to chemotherapy by expressing CDD, have also been observed in patients with pancreatic cancer [ 75 ]. This observation suggests the ability of bacteria from other tissues to affect the resistance to and efficacy of chemotherapy [ 76 ].…”
Section: The Relationship Between Microbiome and Resistance To Chemotherapymentioning
confidence: 99%
“…Elevated levels of oral pathogens Agregatibacter actinomycetemcomitans and Porphyromonas gingivalis , which may affect resistance to chemotherapy by expressing CDD, have also been observed in patients with pancreatic cancer [ 75 ]. This observation suggests the ability of bacteria from other tissues to affect the resistance to and efficacy of chemotherapy [ 76 ].…”
Section: The Relationship Between Microbiome and Resistance To Chemotherapymentioning
confidence: 99%
“…Regardless of their mechanism of action, chemotherapy medications affect all rapidly dividing cells, not just tumor cells. As a result, chemotherapy is frequently linked to high toxicity levels and serious adverse effects [113]. OVs have a higher level of tumor-specificity than chemotherapeutic medications because to both their natural preference for tumor cells and specificity-enhancing genetic changes.…”
Section: Oncolytic Virotherapy In Combination Withmentioning
confidence: 99%
“…In recent years, more and more studies have found that intestinal flora is associated with renal IRI ( Ding et al., 2019 ). There are millions of microorganisms living in the human body ( Liu et al., 2021 ; Lu et al., 2021 ; Wang et al., 2021 ). These microorganisms are widely present in the skin ( Boxberger et al., 2021 ), gastrointestinal tract ( Chen et al., 2021 ), nasal cavity ( Bassis et al., 2014 ), oral cavity ( Blaustein et al., 2021 ) and reproductive tract.…”
Section: Overviewmentioning
confidence: 99%